New data on Cyclocosmia loricata (C.L. Koch, 1842) (Aranei: Halonoproctidae) with first description of the male palp - De Luna, Manuel; Solís Rojas, Carlos; García Barrios, Roberto; Millan, Ana B. (KMK Scientific Press Ltd., 2021)
This article details new records of the trapdoor spider Cyclocosmia loricata (C.L. Koch, 1842) in Nuevo Leon and Tamaulipas states of northeast Mexico, and refutes previous records of C. truncata (Hentz, 1841) for Nuevo Leon. Insight in the variation in rib counts of the disc of the opisthosoma as well as the first description of the male palp are given.